Some Properties of Semi ^# Generalized Open Sets in Topological Spaces - S. Saranya; K. Bageerathi (International Journal of Mathematics And its Applications, 2017)
In this paper a new class of generalized open sets in topological spaces, namely semi ^# generalized open(briefly, s^#g-open) sets is introduced. We prove that this class lies between the class of sg-open sets and the class of gs-open sets and we study some basic properties and characterizations of s^#g-open sets. Also we introduce s^#g-neighbourhood (shortly, s^#-neighbourhood), s^#g-interior, s^#g-closure and s^#g-derived set of a set in a topological spaces and investigate some basic properties of these sets.